LINGUISTIC CRITICISM AS A FIRST PHASE TO LITERARY CRITICISM - Suryo Tri Saksono (Prosodi Jurnal Ilmu Bahasa dan Sastra, 2009)
The aim of this paper is basically methodological: that viewing literature in unusual light—as discourse and thus as communication rather than as object—produces some unusual insights. Thus it is an argument about 'procedure in literate criticism. Because the idea of 'discourse' is to be defined in linguistics, it is an argument about the scope and aims of linguistics too. But beyond these method¬ological considerations, it would sense an implicit political, or at leas: educational, goal also: the approach recommended is designed to make the institution of literature more accessible, to attack an artificial and polemic barrier that has been built between literature and other modes of discourse.